Understanding of EFL Students’ Self-Efficacy in their English Writing Performance - Dhela, Dhela Fika Nuzula Firdausi (ELLITE: Journal of English Language, Literature, and Teaching, 2024)
One of the reasons why students faced some problems and pressures in English writing is some anxieties in the learning process. They need to build self-efficacy to be able to involve their confidence in writing achievement. Teachers should to understand the students’ condition in their self-efficacy before the teaching learning process. This research described the condition of the students’ self-efficacy at twelve grades in Senior High School. A qualitative method by using case study design was used. Using the purposive sampling, 25 students were given self-efficacy open ended questionnaire. Adopting from Bandura’s theory, the result of described students at 12 grades have quite high self-efficacy indicated by their magnitude, generality and strength in writing performance. Magnitude dimension showed the students’ beliefs in passing some difficulties in writing assignment. In Generality dimension, some of the students believe they understand all of the material in writing and affected by their interest. In strength dimension showed all students’ strength by having motivation when students are in failure in writing performance. The present study is an important step in teaching ability to understand students’ self-efficacy for teacher success in their teaching process.